Effects of annealing on the microstructure and mechanical properties of selective laser melted AlSi7Mg alloy - Wang, Min; Song, Bo; Wei, Qingsong; Zhang, Yuanjie; Shi, Yusheng (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2019)
Selective laser melting, due to the high energy density input and the small interaction time (106 K/s), can result in an ultrafine microstructure and excellent mechanical properties. However, due to the nonuniform nature of the temperature distribution and the transition from liquid to solid, high residual stresses exist. High residual stresses in the parts can increase the risk of material distortion and cause many problems, such as dimensional inaccuracy or cracks. This work systematically investigated the influence of annealing on the microstructure and mechanical properties of SLM-processed AlSi7Mg alloy parts. The residual stresses relaxed significantly after annealing. The Vickers hardness and the tensile stress greatly reduced, while the elongation increased. The fracture mode of the as-fabricated sample was ductile and brittle mixed fracture, whereas the fracture morphology of the annealed sample presented many more dimples, and the elongation also increased, which indicated the ductile mode.